The challenges in establishing sustainable supply chain in Bangladesh - Uddin, Mohammad Mazbha (BRAC Univeristy, 2018)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.